Advances in teacher education. Volume 5 : what counts as knowledge in teacher education? - Raths, James D.; McAninch, Amy C. (Advances in teacher education, 1999)
The field of education generally, and teacher education particularly, is experiencing some general disquiet with traditional approaches to the identification and classification of knowledge. Formal research studies, long the source of the knowledge base of teaching, is discredited by new ideologies that are based in the women's movement, the multiculturalists, and persons taken up with newer research strategies called naturalistic, ethnographic, or case study approaches. The book is a collection of essays that rehearses the issues facing the field, and addresses them in forthright fashion.